Is Proton Therapy a “Pro” for Breast Cancer? A Comparison of Proton vs. Non-proton Radiotherapy Using the National Cancer Database - Chowdhary, Mudit; Lee, Anna; Gao, Sarah; Wang, Dian; Barry, Parul N.; Diaz, Roberto; Bagadiya, Neeti R.; Park, Henry S.; Yu, James B.; Wilson, Lynn D.; Moran, Meena S.; Higgins, Susan A.; et al. (Frontiers in Oncology, 2019)
Background: Limited data exists demonstrating the clinical benefit of proton radiotherapy (PRT) in breast cancer. Using the National Cancer Database, we evaluated predictors associated with PRT use for patients with breast cancer. An exploratory analysis also investigates the impact of PRT on overall survival (OS). Methods: Patients with non-metastatic breast cancer treated with adjuvant radiotherapy from 2004 to 2014 were identified. Patients were stratified based on receipt of PRT or non-PRT (i.e., photons ± electrons). A logistic regression model was used to determine predictors for PRT utilization. For OS, Multivariable analysis (MVA) was performed using Cox proportional hazard model. Results: A total of 724,492 patients were identified: 871 received PRT and 723,621 received non-PRT. 58.3% of the PRT patients were group stage 0–1. Median follow-up time was 62.2 months. On multivariate logistic analysis, the following factors were found to be significant for receipt of PRT (all p < 0.05): academic facility (odds ratio [OR] = 2.50), South (OR = 2.01) and West location (OR = 12.43), left-sided (OR = 1.21), ER-positive (OR = 1.59), and mastectomy (OR = 1.47); pT2-T4 disease predicted for decrease use (OR = 0.79). PRT was not associated with OS on MVA for all patients: Hazard Ratio: 0.85, p = 0.168. PRT remained not significant on MVA after stratifying for subsets likely associated with higher heart radiation doses, including: left-sided (p = 0.140), inner-quadrant (p = 0.173), mastectomy (p = 0.095), node positivity (p = 0.680), N2-N3 disease (p = 0.880), and lymph node irradiation (LNI) (p = 0.767). Conclusions: Receipt of PRT was associated with left-sided, ER+ tumors, mastectomy, South and West location, and academic facilities, but not higher group stages or LNI. PRT was not associated with OS, including in subsets likely at risk for higher heart doses. Further studies are required to determine non-OS benefits of PRT. In the interim, given the high cost of protons, only well-selected patients should receive PRT unless enrolled on a clinical trial.